DELVING INTO BEHAVIORAL FINANCE: UNCOVERING THE LINKAGE BETWEEN INVESTMENT PREFERENCE, INVESTOR’S PROFILE, PERSONALITY TRAITS, RISK PERCEPTION, AND INVESTMENT GOALS - Go, Tiffany Ann B; Lim, Vivienne Nicole V; Albao, Marycris O.; Baylon, Dioscoro P. (PEOPLE: International Journal of Social Sciences, 2020)
Investment is a popular economic vehicle where, in the hope of producing more revenue, people invest their capital. Investors are expected to make investment decisions that maximize returns. This study conducted a survey of 96 working adults who made investments in stock, bonds, short-term instruments, mutual funds, and/or foreign currencies. It used explanatory variables such as the profile of investors, the perception of risk, personality characteristics, and investment goals. Investment preference was the outcome variable. Significant results revealed that for medium-term investments, only the conservative and moderate investor profiles had a significant relationship with investor preference. Investment goals showed only partial significance.